2017
DOI: 10.15547/tjs.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest life of cut gerbera flowers as affected by salicylic acid and citric acid

Abstract: Effect of salicylic acid (SA) combined with citric acid (CA) on gerbera (Gerbera jamesonii) cut flowers was studied. The study was conducted in a factorial arrangement, carried out in a complete randomized design. The factors were SA (0.5,1.5 and 3 mM) and CA (1.5 and 3 mM). The effects of treatments on the total chlorophyll content, anthocyanin leakage and malondialdehyde content of cut flowers of gerbera were investigated. The results showed that the vase solution containing 1.5 mM SA significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
0
7
0
1
Order By: Relevance
“…These indicated that the ascorbic acid did not direct the color change into certain color type. The changes of flower color when wilting during vase life were also reported on orchid (Khan, Mehraj, Taufique, Ahsan, & Jamaluddin, 2015), gerbera (Heidarnezhadian, Eghbali, & Kazemi, 2017), rose (Zamani, Kazemi, & Aran, 2011) and carnation (Kazemi, Gholami, & Bahmanipour, 2012). The change of floret color was associated with the decreased carbohydrate content used for respiration and supply due to low photosynthetic rates during vase life period (Ichimura, 1998).…”
Section: Characteristic Of Wilting and Floret Color Changementioning
confidence: 78%
See 1 more Smart Citation
“…These indicated that the ascorbic acid did not direct the color change into certain color type. The changes of flower color when wilting during vase life were also reported on orchid (Khan, Mehraj, Taufique, Ahsan, & Jamaluddin, 2015), gerbera (Heidarnezhadian, Eghbali, & Kazemi, 2017), rose (Zamani, Kazemi, & Aran, 2011) and carnation (Kazemi, Gholami, & Bahmanipour, 2012). The change of floret color was associated with the decreased carbohydrate content used for respiration and supply due to low photosynthetic rates during vase life period (Ichimura, 1998).…”
Section: Characteristic Of Wilting and Floret Color Changementioning
confidence: 78%
“…The change of floret color was associated with the decreased carbohydrate content used for respiration and supply due to low photosynthetic rates during vase life period (Ichimura, 1998). Carbohydrate was one of the main compounds in pigment biosynthesis process and other secondary metabolites, including anthocyanins (Khan et al, 2015;Heidarnezhadian et al, 2017;Zamani et al, 2011). However, ascorbic acid was predicted to have relation in slowing down the process of color change along with the induction of prolonged flower freshness during vase life.…”
Section: Characteristic Of Wilting and Floret Color Changementioning
confidence: 99%
“…These findings reconfirmed 2019) using the same standard type cultivar. Changes in the floret colour after wilting were reported in several cut flowers like orchids (Khan et al 2015), gerberas (Heidarnezhadian et al 2017), roses (Zamani et al 2011) and so on. According to Ichimura (1998), the colour change in a wilted floret is related to the decrease in carbohydrate content in the flower stalks.…”
Section: Characteristics Of the Wilted Leaves/petals And Floret Colou...mentioning
confidence: 96%
“…On the other hand, the supply of assimilates was also limited, since the photosynthetic activity also diminished (Khan et al 2015). During this situation, the pigment biosynthesis was then also considered lower and resulted in the alteration of the floret colour (Zamani et al 2011;Heidarnezhadian et al 2017). Ascorbic acid and salicylic acid play an important role in slowing down the anthocyanin degradation (Heidarnezhadian et al 2017;Obadamudalige et al 2019).…”
Section: Characteristics Of the Wilted Leaves/petals And Floret Colou...mentioning
confidence: 99%
“…SA is a phenolic compound occurring ubiquitously in plants ( Singh et al, 2018 ). It is widely used plant growth regulator which is also effective in other forms in plants such as acetyl salicylic acid and methyl salicylate ( Heidarnezhadian et al, 2017 ). It is synthesized in plants via shikimate pathway by two metabolic routes viz, phenylalanine route and isochorismate route.…”
Section: Introductionmentioning
confidence: 99%